Influence of Online Learning on The Development of Social Capital Students of Class X SMA Negeri 13 Bandung - Rossi Dwi Ameliantie; Sri Wahyuni Tanshzil (Department of Civic Education, 2021)
Online learning is an intermediary that bridges the delivery of teacher information to students through the network. Utilization of network through interaction during the implementation of online learning can be used as an opportunity to develop students' social capital. This study aims to determine the effect of online learning in the process of developing students' social capital in civic education. This study uses a quantitative approach with a descriptive method. The data collection technique was carried out by distributing questionnaires using a Likert scale, which had been tested for validity and reliability, as well as correlation tests and simple linear regression tests to test the effect of online learning on the development of students' social capital, and partial t-tests to test hypotheses. The results showed that online learning had a positive and significant effect on the development of students' social capital with a level of influence of 27.9%. The development of social capital in online learning forms students into good citizens, critical citizens, and can participate actively in solving all challenges and problems that exist within the scope of citizenship.